Hyperuricemia and the cardio-reno-metabolic continuum in chronic kidney disease - I. T. Murkamilov; K. A. Aitbaev; V. V. Fomin; Zh. A. Murkamilova; Z. R. Raimzhanov; Sh. Sh. Khakimov; I. U. Abdurakhmanov; J. I. Solizhonov; T. F. Yusupova; Z. F. Yusupova; A. F. Yusupov; F. A. Yusupov; et al. (Clinical Medicine (Russian Journal), 2026)
Objective. To investigate the relationship between serum uric acid levels and echocardiographic (EchoCG) parameters, and to assess the association of hyperuricemia with cardiovascular and renal abnormalities in patients with chronic kidney disease (CKD). Material and methods. A cross-sectional retrospective study included clinical, instrumental, laboratory, and EchoCG data from 473 patients (307 men and 166 women) with a confi rmed diagnosis of CKD. The mean age of the study participants was 38.5 ± 12.7 years. Hyperuricemia was defi ned as serum uric acid ≥ 0.42 mmol/L in men and ≥ 0.36 mmol/L in women. Patients were divided into subgroups: CKD with hyperuricemia (n = 199) and CKD without hyperuricemia (n = 274). Results. Among all patients with CKD (n = 473), hyperuricemia was observed in 199 cases (42.0%). Compared with patients without hyperuricemia, those with CKD and hyperuricemia had signifi cantly higher mean age, body mass index, systolic and diastolic blood pressure the size of cardiac structures according to ECHOCG data and serum creatinine levels were statistically significantly higher. In contrast, hemoglobin concentration, red blood cell count, and estimated glomerular fi ltration rate (eGFR) were significantly lower. Signifi cant correlations of serum uric acid were found with systolic and diastolic blood pressure, eGFR, left atrial anteroposterior diameter, left ventricular end-systolic and end-diastolic diameter, interventricular septum thickness, posterior wall thickness of the left ventricle, left ventricular ejection fraction, and venous blood glucose. Conclusion. The study demonstrated a signifi cant contribution of hyperuricemia to alterations in the geometry of the left heart chambers and a decline in renal filtration function.